2018
DOI: 10.1289/ehp1912
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Methylated Metabolites of Arsenic and Selenium in Urine of Pregnant Bangladeshi Women and Interactions between the Main Genes Involved

Abstract: Background:It has been proposed that interactions between selenium and arsenic in the body may affect their kinetics and toxicity. However, it is unknown how the elements influence each other in humans.Objectives:We aimed to investigate potential interactions in the methylation of selenium and arsenic.Methods:Urinary selenium (U-Se) and arsenic (U-As) were measured using inductively coupled plasma mass spectrometry (ICPMS) in samples collected from pregnant women (n=226) in rural Bangladesh at gestational week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Animals may have a redundant metabolic system against the biologically and toxicologically ambivalent nutrient, Se. The genetic polymorphism of INMT was also reported. , Our findings support the literature addressing that the amount of TMSe in urine is dependent on the genetic polymorphism of INMT and suggest that INMT is actually required in Se excretion in humans.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Animals may have a redundant metabolic system against the biologically and toxicologically ambivalent nutrient, Se. The genetic polymorphism of INMT was also reported. , Our findings support the literature addressing that the amount of TMSe in urine is dependent on the genetic polymorphism of INMT and suggest that INMT is actually required in Se excretion in humans.…”
Section: Discussionsupporting
confidence: 89%
“…Indolethylamine N -methyltransferase (INMT) is another methyltransferase that catalyzes double methylation of tryptamine to produce N , N -dimethyltryptamine . The TMSe concentration in blood and urine correlated with single nucleotide polymorphisms in the INMT gene by a genome wide association study between the TMSe-producing and nonproducing individuals. , Previous works suggested that mouse and human INMT proteins drove the methylation of dimethylsulfide, dimethylselenide, and dimethyltelluride as substrates. , However, it is still unclear how INMT commits to produce TMSe for urinary Se excretion.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolism of arsenic changes throughout the course of pregnancy. 25,26 The first trimester was suggested to be the critical period of arsenic exposure in the etiology of GDM. 15,27 Thus, it is important to investigate arsenic species and methylation capacity in the first trimester to adequately explore the relationship between arsenic methylation and GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies compared the methylation indices between GDM and non-GDM groups and found no significant differences. , These studies, however, have only focused on urine samples collected in the second trimester when an oral glucose tolerance test (OGTT) was taken. The metabolism of arsenic changes throughout the course of pregnancy. , The first trimester was suggested to be the critical period of arsenic exposure in the etiology of GDM. , Thus, it is important to investigate arsenic species and methylation capacity in the first trimester to adequately explore the relationship between arsenic methylation and GDM.…”
Section: Introductionmentioning
confidence: 99%